Obesidade induzida após o desmame potencializa o efeito nefrotóxico da cisplatina - Ribeiro, Rosemara Silva [UNIFESP] (2016)
Overweight establishes a charge on the kidney resulting in increased glomerular filtration rate (GFR) and renal hypertrophy may accelerate the damage of renal function. The renal effects of obesity in adult individual are well explored, less is known on the impact of childhood obesity in the kidney in adult life, and if this event can exacerbate the renal response to an acute injury. The objectives of this study were: evaluate the impact of the obesity established in mice during childhood on renal function in adult life and evaluate if metabolic condition potentiate the nephrotoxic effects of cisplatin. C57BL/6 mice at 21 days age (postweaning) were divided into group control (CT), fed with standard diet, and high fat diet group (HF), fed with high fat diet. After 9 weeks the animals were divided into groups: CT, CT treated with cisplatin (CTCis), HF and HF treated with cisplatin (HFCis). Cisplatin was administered in single dose of 20 mg/kg (i.p.). After 72 hours the animals were anesthetized and blood and tissues (kidneys and visceral fat) were used for biochemical, molecular and histology analysis. The HF group exhibited higher body weight gain, increased visceral adiposity, hyperkalemia, sodium retention, glomerular hyperfiltration, proteinuria and intrarenal overexpression of the pro oxidant enzyme, gp91phox, indicating renal function responses to the obesity. Cisplatin induced AKI with reduced GFR in both groups, but the effect was exacerbated in obese animals with reduction of 92% versus 31% in the CTCis group, resulting in an expressive serum creatinine and urea accumulation. The HFCis group exhibited systemic and intrarenal inflammation significantly higher than the non obese animals. These results suggest that obese animals were more susceptible to the nephrotoxic effects induced by cisplatin resulting in greater severity of AKI.